Regulation of lung inflammation by adiponectin - Lim, Joo-Yeon; Templeton, Steven P. (Frontiers in Immunology, 2023)
Adiponectin is an insulin sensitizing hormone that also plays a role in the regulation of inflammation.Although adiponectin can exert pro-inflammatory effects, more studies have reported anti-inflammatory effects, even in non-adipose tissues such as the lung. Obesity is considered an inflammatory disease, is a risk factor for lung diseases, and is associated with decreased levels of plasma adiponectin. The results of recent studies have suggested that adiponectin exerts anti-inflammatory activity in chronic obstructive pulmonary disease, asthma and invasive fungal infection. The signaling receptors of adiponectin, AdipoR1 and AdipoR2, are expressed by epithelial cells, endothelial cells, and immune cells in the lung.In this mini-review, we will discuss the anti-inflammatory mechanisms of adiponectin in lung cells and tissues.